Placental histological examination and the relationship with oxidative stress in preterm infants. (October 2016) - Perrone, Serafina; Tataranno, Maria Luisa; Negro, Simona; Longini, Mariangela; Toti, Maria Stefania; Alagna, Maria Gabriella; Proietti, Fabrizio; Bazzini, Francesco; Toti, Paolo; Buonocore, Giuseppe
Abstract: Background: Prenatal conditions of enhanced oxidative stress (OS) linked to inflammation or hypoxia have been associated with impaired fetal growth and preterm delivery. Little is known regarding biomarkers of OS in the cord blood of preterm infants and placental histological patterns. Objectives: To test the hypothesis that placental lesions indicating chorioamnionitis (CA) or vascular underperfusion (VU) are associated with increased OS in the offspring. Methods: 120 neonates born below 29 +6 weeks of gestational age (GA) were enrolled. Histological characteristics of placentas from their mothers were classified as normal (CTRL group), histological CA (HCA) and vascular underperfusion (VU). Serum concentrations of isoprostanes (IsoPs), non-protein bound iron (NPBI) and advanced oxidative protein products (AOPP), were determined in cord blood. Results: IsoPs, NPBI and AOPP were significantly increased in HCA group compared to CTRL group. The multivariable regression model, adjusted for GA, maternal age, parity, maternal diabetes, maternal obesity and presence/absence of fetal growth restriction (FGR), showed a significant association between the presence of HCA and increased OS biomarkers levels in cord blood (IsoPs: p  = 0.006; NPBI: p  = 0.014; AOPP: p  = 0.007). Placental VU lesions were significantly associated with higher umbilical IsoPs, NPBI and AOPP levels (IsoPs: p  = 0.008; NPBI: p  = 0.002; AOPP: p  = 0.040). In the cases of placental VU lesions associations were also found between high AOPP levels and low GA ( p  = 0.002) and the presence of fetal growth restriction ( p  = 0.014). Conclusions: Placental lesions indicating inflammation or impaired perfusion are associated with higher cord blood levels of OS biomarkers explaining the fetal susceptibility to oxidative injury and the need of antioxidant protection. Highlights: A relationship between placental lesions and cord blood oxidative stress was found. Oxidative stress builds up in response to inflammation or impaired perfusion stimuli. Free iron, lipid and protein oxidation products were the most reliable markers. The risk of placental oxidative injury to newborns should be identify early at birth.